78+3x=10x-97

Simple and best practice solution for 78+3x=10x-97 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 78+3x=10x-97 equation:


Simplifying
78 + 3x = 10x + -97

Reorder the terms:
78 + 3x = -97 + 10x

Solving
78 + 3x = -97 + 10x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-10x' to each side of the equation.
78 + 3x + -10x = -97 + 10x + -10x

Combine like terms: 3x + -10x = -7x
78 + -7x = -97 + 10x + -10x

Combine like terms: 10x + -10x = 0
78 + -7x = -97 + 0
78 + -7x = -97

Add '-78' to each side of the equation.
78 + -78 + -7x = -97 + -78

Combine like terms: 78 + -78 = 0
0 + -7x = -97 + -78
-7x = -97 + -78

Combine like terms: -97 + -78 = -175
-7x = -175

Divide each side by '-7'.
x = 25

Simplifying
x = 25

See similar equations:

| 6/z-3/z=15 | | 2(2x-3)=4(2x+2) | | 12-x/2=x/5 | | 2x-5/12-3x/6=11/12 | | 4x^2-2x+30=0 | | 5x+35=86 | | 13=3(x-4)-(x-9) | | 76+6x=-11x-145 | | G(x)=2x+1 | | 0.5x+1.9=0.8x-0.2 | | (4x-9z)(3x+5z)= | | 7x-20=33 | | (x^6y^-3/z^-1)-5 | | 0.19x+0.2(x-4)=0.01(5x-2) | | kx^2+k=8x-2xk | | 4(x-3)+1=6x-2(4+x) | | 1.67u-1.67=1.25-.67 | | 1.5x=x+15 | | 0.12(y-7)+0.18y=0.10y-0.6 | | .9y-3.6=-.3y+3 | | 7x-7=8+6x | | 3(4y+4)=10 | | 28x+35=8x-27 | | 4m=(m+4)(2-m) | | 14x-2=-3x-18 | | 7.25x+5.4y=730 | | 5.7x-3.1(x+5)=5.04 | | -2x/3-2-3 | | -[3z-(5z+8)]=8+(1z+7) | | 15x-25=4x+2 | | -15w+15=-15w+15 | | 9x+5=-8+3x+25 |

Equations solver categories